2023
DOI: 10.1124/dmd.122.001131
|View full text |Cite
|
Sign up to set email alerts
|

Activation/Inactivation of Anticancer Drugs by CYP3A4: Influencing Factors for Personalized Cancer Therapy

Abstract: Cytochrome P450 3A4 (CYP3A4), one of the most important members of the cytochrome P450 subfamily, is a crucial catalyst in the metabolism of numerous drugs. As it catalyzes numerous processes for drug activation or inactivation, the pharmacological activities and clinical outcomes of anticancer drugs metabolized by CYP3A4 are highly dependent on the enzyme's activity and expression. Due to the complexity of tumor microenvironments and various influencing factors observed in human in vitro models and clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 183 publications
0
2
0
1
Order By: Relevance
“…In contrast, prodrugs might require a lower dose due to increased formation of active metabolites and the risk of increased plasma concentrations and toxicity. This would be particularly relevant for anticancer drugs that are activated/inactivated by CYP3A4 and have a narrow therapeutic range 30 . This might also be relevant for long‐term treatment with flucloxacillin, as shown for warfarin, 10 but this will depend on the pharmacokinetic properties of the victim drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, prodrugs might require a lower dose due to increased formation of active metabolites and the risk of increased plasma concentrations and toxicity. This would be particularly relevant for anticancer drugs that are activated/inactivated by CYP3A4 and have a narrow therapeutic range 30 . This might also be relevant for long‐term treatment with flucloxacillin, as shown for warfarin, 10 but this will depend on the pharmacokinetic properties of the victim drug.…”
Section: Discussionmentioning
confidence: 99%
“…This would be particularly relevant for anticancer drugs that are activated/inactivated by CYP3A4 and have a narrow therapeutic range. 30 This might also be relevant for long-term treatment with flucloxacillin, as shown for warfarin, 10 but this will depend on the pharmacokinetic properties of the victim drug. Although not directly comparable, our results on CYP3A4 align with our previously published in vitro study 3 and observational data, 5,6,10,24 which have indicated that flucloxacillin is a less potent inducer of CYP enzymes than dicloxacillin.…”
Section: Articlementioning
confidence: 99%
“…Furthermore, CYPs have also been shown to detoxify anticancer drugs. For instance, tamoxifen, taxanes, teniposide, gefitinib, imatinib, vinca alkaloids, and sorafenib are some drugs metabolized by CYP3A4 [ 70 ] . Another example is CYP2B6 mutations that are linked to a poor response to cyclophosphamide-based treatment in breast cancer patients, whereas CYP2D6 mutations frequently limit the anticancer effect of tamoxifen [ 71 ] .…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…Coadministration with potent CYP inhibitors or inducers may trigger pharmacokinetic drug/herb-drug interactions (DDIs/HDIs), resulting in drug accumulation or treatment failure, especially for the patients receiving some narrow therapeutic index medications (such as warfarin, digoxin, ciclosporin, etc.) (Kalra, 2007;Kumar et al, 2012;Wang et al, 2023). As a non-negligible cause of adverse drug reactions (ADRs), DDI/HDI may bring many undesirable effects or even result in deaths (Kalra, 2007;Kumar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%